HUBUNGAN ANTARA KECENDERUNGAN ADIKSI MEDIA SOSIAL TIKTOK DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA FAKULTAS ILMU PENDIDIKAN DAN PSIKOLOGI UNIVERSITAS NEGERI MANADO - Agnes Martinu, Gabriella; Becher Sengkey, Stevi; Naharia, Melkian (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The development of digital technology and the widespread use of social media, particularly TikTok, have transformed students’ interaction patterns and learning behaviors. TikTok is not only used as a source of entertainment but can also trigger addictive tendencies that may negatively impact academic activities, including academic procrastination. This study aims to examine the relationship between the tendency toward TikTok social media addiction and academic procrastination among students of the Faculty of Education and Psychology at Manado State University. This research employs a quantitative approach with a correlational method. From a population of 2,554 students, a total of 245 respondents were obtained through purposive sampling. The instruments used were the Social Media Addiction Scale–Student Form to measure TikTok social media addiction (α = 0.970) and the Multidimensional Academic Procrastination Scale to measure academic procrastination (α = 0.920). Data were analyzed using Pearson correlation and simple linear regression through SPSS version 25. The findings indicate a positive and significant relationship between TikTok addiction and academic procrastination (r = 0.566; p < 0.05). The coefficient of determination (R² = 0.321) shows that 32.1% of the variation in academic procrastination is influenced by the level of TikTok addiction, while the remaining 67.9% is affected by other factors. These results suggest that the higher the level of TikTok addiction, the greater the tendency for students to delay academic tasks. This study highlights the importance of managing social media usage, strengthening digital literacy education, and applying healthy learning strategies to prevent the negative impacts of social media addiction. The results are expected to serve as a reference for educational institutions in designing interventions that support students’ well-being and academic performance in the digital era.